Development of the Teaching Process in Primary Education - Mamarasulova Gulshodaxon Dilshodbek qizi (Research Parks Publishing LLC, 2021)
Today, quality education is essential for all sectors of development. Teachers' growth has become a demand of the times at a time when the area of education is continually evolving. Uzbekistan's education system is progressively using technology and digital networks. As time passes and technology advances, improving the quality of primary education will necessitate renewal, development, and training. This article examines the primary school teaching process, as well as the characteristics of education in the twenty-first century and the elements that influence it, as well as the evolution of the primary school teaching process under their influence.